Benign Familial Neonatal Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Linkage studies with the chromosome 20 markers D20S19 and D20S20 were performed in two families with benign familial neonatal convulsions at the Department of Pediatrics, The University of Texas Health Science Center, San Antonio, TX.